THE EFFECT OF GREEN PRACTICES ON EMOTIONAL ATTACHMENT AND GREEN LOYALTY OF COFFEE SHOP CONSUMERS (TURKEY)* - Bekar, Aydan; Durmaz, Şükran; Yozukmaz, Nisan (Turizam, 2020)
As individuals have recently become more sensitive towards environmental issues, green marketing has emerged as an important strategic tool in order to gain competitive advantage for hospitality and food and beverage enterprises. This study is aimed at determining the effect of green marketing practices on coffee shop customers’ loyalty and emotional attachment. For this aim, the customers of 3 Starbucks (coffee shop) operating in Mugla province (Turkey) and having Leadership in Energy and Environmental Design (LEED) Certificate (n=404) were included in the scope of this study. The hypotheses determined for this aim were tested via path analysis with latent variables which was one of the structural equation modellings. According to test results, it was concluded that green practices had a positive significant effect on attachment to green businesses; customer attachment to green businesses had a positive significant effect on green loyalty to both green businesses and green products and also loyalty towards green businesses had a negative impact on loyalty towards green products. These results show that it is important for food and beverage businesses to adopt green practices both for raising awareness towards environmental protection and also for creating customer loyalty and emotional attachment. In this way, environmentally friendly practices provide competitive advantage as well as an increase in the number of environmentally friendly customers for businesses.